An Industry 4.0 Asset Administration Shell-Enabled Digital Solution for Robot-Based Manufacturing Systems - Xun Ye (IEEE, 2021)
The increasing penetration of cyber-physical system (CPS) technologies in industry is transforming this environment into a multifaceted system featuring a tight combination of its physical and computational elements, including their digital (virtual) representations, contributing to the concept of an industrial CPS. The German “Industry 4.0” is a key innovation program aimed at realizing industrial CPS. Industry 4.0 is characterized by digital industrial components interacting with each other to become systems meeting flexible industrial demands, e.g., order-controlled production. An asset administration shell (AAS), as defined in the context of the Reference Architectural Model for Industry 4.0 (RAMI 4.0), is a practical embodiment of the latest buzzword, digital twin, and can be realized with the integration of operation technologies and information and communication technologies. AASs offer an interoperable way to capture key information pertaining to assets, such as intrinsic properties, operational parameters, and technical functionalities, and to enable straightforward interaction over standardized, secure communication with other Industry 4.0 components. The goal of this article is to present the status quo of AAS development, to design an intuitive method for implementing AASs, and to develop an AAS-enabled digital solution for cyber-physical applications in the manufacturing sector. Last but not least, we demonstrate a case study featuring an Industry 4.0 application scenario, i.e., plug-and-produce.